Seeds of contention: world hunger and the global controversy over genetically modified crops [In Chinese] - Pinstrup-Andersen, Per; Schioler, Ebbe (Chinese Academy of Agricultural Sciences, 2001)
The authors assess the role various strategies can play in augmenting global food supplies and combating hunger.They attempt to defuse the contentious debate surrounding the development and spread of genetically modified (GM) foods, which, they argue, can help meet the needs of the poor.The authors recommend a cautious approach that would encourage innovation but respect sound scientific procedures that guard against risks to humans and the environment.